2021
DOI: 10.1159/000512715
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Stroke Risk Factors and Signs in Parakou, a Northern City of Benin in West Africa

Abstract: <b><i>Introduction:</i></b> We aimed to determine knowledge of stroke risk factors and signs in an urban population of northern Benin. <b><i>Methods:</i></b> A door-to-door purposeful sampling survey was conducted in resident population (age ≥15 years) of the district of Titirou in the city of Parakou (<i>N</i> = 255,478) in Benin between March 15 and July 15, 2016. In-person interviews were conducted with data collection on structured questionnaires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
1
0
0
Order By: Relevance
“…9,33,40 With regard to stroke symptoms, participants in our study expressed a high percentage recalling at least one stroke symptom (89.9%) compared to studies in Jordan (95.5%), 9 Iraq (76.2%), 33 Portugal (74.2%), 41 Norway (70.7%), 42 Canada (69.5%), 43 Oman (68.0%), 44 Korea (65%), 45 Lebanon (68.2%), 10 and Benin of west Africa (4.9%). 35 In contrast to our study, only (23%) of participants in a prior 2007 study among GCC countries, including the UAE, identified at least one sign or symptom connected to stroke, which is still a low percentage. 22 Sudden difficulty speaking or understanding speech was the most frequently reported stroke symptom in our study (78.0%) with same symptom reported in previous studies in Jordan (92.3%), 9 Iraq (88.0%), 33 China (65.2%), 46 Saudi Arabia (63.8%), 39 Ireland (54%), 11 and Australia (14.2%).…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…9,33,40 With regard to stroke symptoms, participants in our study expressed a high percentage recalling at least one stroke symptom (89.9%) compared to studies in Jordan (95.5%), 9 Iraq (76.2%), 33 Portugal (74.2%), 41 Norway (70.7%), 42 Canada (69.5%), 43 Oman (68.0%), 44 Korea (65%), 45 Lebanon (68.2%), 10 and Benin of west Africa (4.9%). 35 In contrast to our study, only (23%) of participants in a prior 2007 study among GCC countries, including the UAE, identified at least one sign or symptom connected to stroke, which is still a low percentage. 22 Sudden difficulty speaking or understanding speech was the most frequently reported stroke symptom in our study (78.0%) with same symptom reported in previous studies in Jordan (92.3%), 9 Iraq (88.0%), 33 China (65.2%), 46 Saudi Arabia (63.8%), 39 Ireland (54%), 11 and Australia (14.2%).…”
Section: Discussioncontrasting
confidence: 97%
“…In comparison, previous studies have reported 98.1% among 573 participants in Jordan, 9 85.4% among 5391 participants in first study in Lebanon, 10 and 97.8% among 551 participants in the second study in Lebanon, 32 76.2% among 822 participants in Australia, 28 76.2% among 609 participants in Iraq, 33 59.6% among 2,884 participants in Spain, 34 and 8.6% among 4,671 participants in Benin of West Africa. 35 Conversely, other previous studies have demonstrated poor knowledge of stroke risk factors and symptoms in the general population. 7,36,37 High blood pressure, hyperglycemia, obesity, renal dysfunction, and hyperlipidemia are all risk factors for stroke, according to the American Heart Association's latest update for 2021, with a further (47%) attributed to behavioral risk factors like sedentary behavior, smoking, and an unhealthy diet.…”
Section: Discussionmentioning
confidence: 96%
“…On the whole, knowledge of warning signs and stroke risk factors was poor among the stoke patients in this study. This finding was aligned with the earlier research concentrating on participants with high blood pressure, which reported that their knowledge level of warning signs and risk factors related to stroke was inadequate ( Bhat et al, 2021 , Houessou et al, 2021 , Melak et al, 2021 ). However, the proportion was lower than the previous research conducted among hypertension patients in Ethiopia (40.7%) ( Woldetsadik et al, 2022 ).…”
Section: Discussionsupporting
confidence: 88%
“…Male participants had better knowledge than female. The most identified risk factor was 'unhealthy lifestyle' and the least identified one was 'epilepsy' and 86.6% of the participants agreed that stroke is a medical emergency [9] .  A cross sectional study was conducted to assess the community stroke awareness on knowledge attitude and health seeking behaviour among adults in urban slums of Hyderabad.…”
Section: Review Of Literature Related To Knowledge On Strokementioning
confidence: 99%